Oxidative stress in aquatic ecosystems - Abele, Doris (Wiley-Blackwell, 2012)
"Reactive oxygen species (ROS) are increasingly appreciated as down-stream effectors of cellular damage and dysfunction under natural and anthropogenic stress scenarios in aquatic systems. This comprehensive volume describes oxidative stress phenomena in different climatic zones and groups of organisms, taking into account specific habitat conditions and how they affect susceptibility to ROS damage.A comprehensive and detailed methods section is included which supplies complete protocols for analyzing ROS production, oxidative damage, and antioxidant systems. Methods are also evaluated with respect to applicability and constraints for different types of research.The authors are all internationally recognized experts in particular fields of oxidative stress research.This comprehensive reference volume is essential for students, researchers, and technicians in the field of ROS research, and also contains information useful for veterinarians, environmental health professionals, and decision makers"--